Contingent Effects of Liming on N2O-Emissions Driven by Autotrophic Nitrification - Nadeem, Shahid; Bakken, Lars R.; Frostegård, Åsa; Gaby, John C.; Dörsch, Peter (Frontiers in Environmental Science, 2020)
Liming acidic soils is often found to reduce their N2O emission due to lowered N2O/(N2O+N2) product ratio of denitrification. Some field experiments have shown the opposite effect, however, and the reason for this could be that liming stimulates nitrification-driven N2O production by enhancing nitrification rates, and by favoring ammonia oxidizing bacteria (AOB) over ammonia oxidizing archaea (AOA). AOB produce more N2O than AOA, and high nitrification rates induce transient/local hypoxia, thereby stimulating heterotrophic denitrification. To study these phenomena, we investigated nitrification and denitrification kinetics and the abundance of AOB and AOA in soils sampled from a field experiment 2 - 3 years after liming. The field trial compared traditional liming (carbonates) with powdered siliceous rocks. As expected, the N2O/(N2O+N2) product ratio of heterotrophic denitrification declined with increasing pH, and the potential nitrification rate and its N2O yield (YN2O: N2O-N/NO3– N), as measured in fully oxic soil slurries, increased with pH, and both correlated strongly with the AOB/AOA gene abundance ratio. Soil microcosm experiments were monitored for nitrification, its O2-consumption and N2O emissions, as induced by ammonium fertilization. Here we observed a conspicuous dependency on waterfilled pore space (WFPS): at 60 and 70% WFPS, YN2O was 0.03-0.06% and 0.06-0.15%, respectively, increasing with increasing pH, as in the aerobic soil slurries. At 85% WFPS, however, YN2O was more than two orders of magnitude higher, and decreased with increasing pH. A plausible interpretation is that O2 consumption by fertilizer-induced nitrification cause hypoxia in wet soils, hence induce heterotrophic nitrification, whose YN2O decline with increasing pH. We conclude that while low emissions from nitrification in well-drained soils may be enhanced by liming, the spikes of high N2O emission induced by ammonium fertilization at high soil moisture may be reduced by liming, because the heterotrophic N2O reduction is enhanced by high pH.